Effects of light and temperature on growth, nitrate uptake, and Toxin production of two tropical dinoflagellates: alexandrium Tamiyavanichii and alexandrium minutum (dinophyceae) - Po, T.L; Chui, P.L; Usup, G.; Kobiyama, A.; Koike, K.; Ogata, T. (Blackwell Publishing, 2006)
The two tropical estuarine dinoflagellates, Alexandrium tamiyavanichii Balech and A. minutum Halim, were used to determine the ecophysiological adaptations in relation to their temperate counterparts. These species are the two main causative organisms responsible for the incidence of paralytic shellfish poisoning (PSP) in Southeast Asia. The effects of light (10, 40, 60, and 100 lmol photons .m_2 . s_1) and temperature (15, 20, and 251 C) on the growth, nitrate assimilation, and PST production of these species were investigated in clonal batch cultures over the growth cycle. The growth rates of A. tamiyavanichii and A. minutum increased with increasing temperature and irradiance. The growth of A. tamiyavanichii was depressed at lower temperature (201 C) and irradiance (40 lmol photons .m_2 . s_1). Both species showed no net growth at 10 lmol photons .m_2 . s_1 and a temperature of 151 C, although cells remained alive. Cellular toxin quotas (Qt) of A. tamiyavanichii and A. minutum varied in the range of 60–180 and 10–42 fmol PST. cell_1, respectively. Toxin production rate, Rtox, increased with elevated light at both 20 and 251 C, with a pronounced effect observed at exponential phase in both species (A. tamiyavanichii, r250.95; A. minutum, r250.96). Toxin production rate also increased significantly with elevated temperature (P<0.05) for both species examined. We suggest that the ecotypic variations in growth adaptations and toxin production of these Malaysian strains may reveal a unique physiological adaptation of tropical Alexandrium species.